2002
DOI: 10.1046/j.1537-2995.2002.00002.x
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of the Knops blood group system and subdivision of Sla

Abstract: The antigen formerly known as Sl(a) can now be subdivided. A new terminology is proposed that recognizes both linear and conformational epitopes on the CR1 protein. At amino acid 1601, Sl 1 (Sl(a)) is represented by R, Sl 2 (Vil) is represented by glycine, and Sl 3 requires both R1601 and S1610. Sl 4 and Sl 5 are hypothetical epitopes represented by S1610 and T1610, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 18 publications
(18 reference statements)
1
31
1
Order By: Relevance
“…Several antigens have been described in the Knops blood group system on CR1; Knops antigens a and b (Kn a /Kn b ), rs41274768 [19], McCoy a and b (McC a /McC b ), rs17047660 [20], Swain-Langley 1 and 2 (Sl1/Sl2), rs17047661 [20,21], KCAM + and - (KCAM + /KCAM - ), rs6691117 [22], York + and - (Yka + /Yka - ), rs3737002 [23] and Sl3,rs4844609 [21]. …”
Section: Introductionmentioning
confidence: 99%
“…Several antigens have been described in the Knops blood group system on CR1; Knops antigens a and b (Kn a /Kn b ), rs41274768 [19], McCoy a and b (McC a /McC b ), rs17047660 [20], Swain-Langley 1 and 2 (Sl1/Sl2), rs17047661 [20,21], KCAM + and - (KCAM + /KCAM - ), rs6691117 [22], York + and - (Yka + /Yka - ), rs3737002 [23] and Sl3,rs4844609 [21]. …”
Section: Introductionmentioning
confidence: 99%
“…72 A detailed characterization of the molecular basis of most of the Knops system antigens was performed by Moulds and coworkers. [73][74][75] The authors confirmed their data by performing inhibition studies with recombinant CR1 truncations. …”
Section: Cr1 Structure and Expression Patternmentioning
confidence: 53%
“…Another CR1 polymorphism of interest relates to the Knops blood group system. This system consists of nine antigens (KN1-KN9) comprising the three antigenic pairs V1561M, K1590E and R1601G and one conformational epitope (R1601 with S1610) in CCP25, and the single antigens T1408 located in the linker between CCPs 22-23 and I1615 in CCP25 (Table 2) (Covas et al, 2007;Moulds et al, 1991Moulds et al, , 2002Moulds et al, , 2005Veldhuisen et al, 2011).…”
Section: Complement Receptor 1 and Malariamentioning
confidence: 99%